Ocena ryzyka i efektywności inwestycji na rynku metali szlachetnych - Drozd, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Objective — analysis of risk and efficiency of investments in investment funds and insurance capital funds on the precious metals market. The basic research problem was the answer to the question whether investing in investment funds and in insurance capital funds on the precious metals marketis effective and what is the risk involved. The analysed period is not a period of market downturn.The period from 30.09.2014 to 06.10.2019 is analysed. The collected data are weekly.
Keywords: investment funds; insurance capital funds; precious metals market; risk; efficiency